2013
DOI: 10.3727/096368912x657756
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Stem Cells Rescue Both in Vitro and in Vivo Growth, Innervation, and Motility in Nitrofen-Exposed Hypoplastic Rat Lungs through Paracrine Effects

Abstract: Lung hypoplasia can be prevented in vitro by retinoic acid (RA). Recent evidence suggests that amniotic fluid stem (AFS) cells may integrate injured lungs and influence their recovery. We tested the hypothesis that AFS cells might improve lung growth and motility by paracrine mechanisms. Pregnant rats received either nitrofen or vehicle on E9.5. In vitro E13 embryonic lungs were cultured in the presence of culture medium alone or with RA, basophils, or AFS cells. In vivo green fluorescent protein-expressing (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 50 publications
(67 reference statements)
3
50
0
Order By: Relevance
“…Stem cell biology work has also recently postulated "paracrine growth factor"-mediated signalling with amniotic fluid stem cell therapy with in vitro and in vivo experiments in the nitrofen model. 46 These studies greatly mimic the FGF effects observed in hypoplastic lung organ systems by the research team in Liverpool well over a decade ago. 42 The challenge(s) ahead-"can regenerative medicine technologies grow a new lung?"…”
Section: Neurodevelopmentalmentioning
confidence: 82%
“…Stem cell biology work has also recently postulated "paracrine growth factor"-mediated signalling with amniotic fluid stem cell therapy with in vitro and in vivo experiments in the nitrofen model. 46 These studies greatly mimic the FGF effects observed in hypoplastic lung organ systems by the research team in Liverpool well over a decade ago. 42 The challenge(s) ahead-"can regenerative medicine technologies grow a new lung?"…”
Section: Neurodevelopmentalmentioning
confidence: 82%
“…A study by Pederiva and colleagues showed, in the rat nitrofen model of pulmonary hypoplasia, that early prenatal administration of expanded AFSCs improved lung growth, bronchial motility and innervation, both in vitro and in vivo [39]. The salutary effects of AFSC transplantation were related to release and paracrine activity of growth factors including fibroblast growth factor 10 (FGF10) and vascular endothelial growth factor alpha (VEGF-a).…”
Section: Respiratory Systemmentioning
confidence: 97%
“…In 2012, it has been demonstrated that both 1st and 2nd trimester AFS cells can be reprogrammed to functional pluripotent stem cells by culture on Matrigel in ES cell medium supplemented with the histone deacetylase inhibitor (HDACi) valproic acid (VPA), but without ectopic reprogramming factors [38]. AFS cells have shown benefits in several disease models, including spinal muscular atrophy [39], congenital diaphragmatic hernia [40], myocardial infarction [41] and sepsis [42].…”
Section: Amniotic Fluid Stem Cellsmentioning
confidence: 99%